(untitled) (International Educators Conference, 2025)
Stress is a pervasive phenomenon in the lives of students, often manifesting through academic pressure, social dynamics, financial concerns, and personal development challenges. This article explores the physiological, psychological, and behavioral effects of stress on student health and identifies evidence-based prevention strategies. The discussion includes stress’s role in the development of anxiety, depression, sleep disorders, and weakened immune function. Furthermore, the article highlights preventive interventions such as time management training, mindfulness techniques, peer support systems, and institutional reforms. Emphasis is placed on the importance of proactive stress management for maintaining both academic performance and long-term well-being.